Pengembangan instrumen non tes media pembelajaran teori sastra berbasis android menggunakan aplikasi inventor - Hiasa, Fina (Fakultas Sastra Universitas Negeri Malang, 2022)
The purpose of this development research is to produce a non-test instrument in the form of a questionnaire. The resulting questionnaire will later be used as a tool to test the feasibility of Android-based literary theory learning media using the inventor application. The development of this non-test instrument adopts the Research and Development (R&D) method which aims to produce certain products, where the product is a questionnaire. The questionnaire will be distributed to validators to be assessed for content validity (CV). There are 5 questionnaires that will be tested for CV by the validators, namely educator needs analysis questionnaire, student needs analysis questionnaire, material expert validation questionnaire, media expert validation questionnaire, user response questionnaire. The results of the non-test instrument feasibility test in the form of a questionnaire through content validity assessment are as follows; 1) a lecturer needs analysis questionnaire consisting of 6 statement items obtained a cv value of 0.875. Furthermore, the student needs analysis questionnaire consisting of 5 statement items obtained a cv value of 1. The material validation questionnaire consisting of 17 statement items obtained a cv value of 0.9 while the media validation questionnaire was 0.7. Finally, the user response questionnaire obtained a CV of 1. From the CV results of the five questionnaires that the researcher developed, it showed that the non-test instrument in the form of a questionnaire that the researcher developed was feasible to be used as a data collection tool.